THE ANTIBACTERIAL ACTIVITIES OF SOME PLANT DERIVED TRITERPENES - Penduka, D.; Gasa, N.P; Hlongwane, M.S; Mosa, R.A; Osunsanmi, F.O.; A.R., Opoku (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The increase in the prevalence of multi-drug resistant bacteria has necessitated the search for new antimicrobials from alternativesources such as traditional medicinal plants.Materials and Methods: The agar well diffusion method was employed to determine the susceptibilities of four plant derived triterpenes namely,3β-hydroxylanosta-9, 24-dien-21-oic acid (RA5), and methyl-3β-hydroxylanosta-9, 24-dien-21oate (RA3), a mixture of oleanolic acid and betulinicacid (SF1) and a mixture of 3β-acetonyloleanolic acid and 3β-acetonylbetulinic acid (SF2), at a concentration of 10 mg/ml against seven Escherichiacoli, one Bacillus cereus, five Enterococcus and nine Vibrio bacteria. The minimum inhibitory concentration (MIC) and minimum bactericidalconcentration (MBC) were determined through the micro-broth dilution assay. The checkerboard method was used to determine the antibiotictriterpeneinteractions while the cytosolic lactate dehydrogenase test was used to determine the membrane damaging potentials of the triterpenes incomparison to 3% Triton X-100.Results: The triterpenes RA3, RA5, SF1 and SF2 had activities against 86.4%, 54.6%, 22.7% and 9.09% of the test bacteria respectively. SF1 hadthe lowest MIC values ranging 0.625-10 mg/ml with lower MIC values being noted against Gram negative bacteria in comparison to Gram positivebacteria; this trend was also noted among the activities of RA3 and RA5 although they had higher MIC value ranges of 1.25-10 mg/ml and 5- 10mg/ml respectively. MBC studies proved the triterpenes to be mostly bacteriostatic. The interaction studies with ciprofloxacin were mainly rangingbetween indifference and antagonism. RA3 alone showed minimal membrane damaging potential with the levels of cytosolic lactate dehydrogenasereleased ranging from 1-36% in comparison to 3%Triton X-100 against E.coli (DSM-8695) and V. vulnificus (AL 042).Conclusion: The results hereby show the potential that the test triterpenes have as antibacterial agents, especially against the Gram negative bacterianamely E. coli and Vibrio bacteria